Managing Resource-Induced Volatility in Papua New Guinea : Some Issues for Discussion - Izvorski, Ivailo; Ollero, Tony (World Bank, Washington, DC, 2017)
This report reviews developments in Papua New Guinea (PNG) since independence, and looks at the issues relevant for saving and managing natural resources and resource induced volatility. These issues could serve as a useful basis for discussion of options the government of PNG could pursue as it emerges from the economic and financial crisis and looks forward to the start of operation of the PNG liquified natural gas (LNG) project. Although the wealth of international experience suggests several key areas for the attention of the authorities, many issues can be addressed only on the basis of detailed projections about future resource flows and investment outlays. Whether the rules will prove effective will also depend on other steps to enhance the fiscal framework. The World Bank can provide more detailed analysis, expertise and recommendations should such data become available.